A cross‐sectional study of breastfed infants referred for tongue tie assessment and frenotomy in one Canadian health region - Tiffany A. Lee; Jessica Bishop; Anne Drover; William K. Midodzi; Laurie K. Twells (Wiley, 2024)
ABSTRACT Importance Tongue tie (TT) is a condition that can cause infant feeding difficulties due to restricted tongue movement. When TT presents as a significant barrier to breastfeeding, a frenotomy may be recommended. Universally accepted diagnostic criteria for TT are lacking and wide prevalence estimates are reported. New referral processes and a Frenotomy Assessment Tool were implemented in one Canadian health region to connect breastfeeding dyads with a provider for TT evaluation and frenotomy. Objective To determine the proportion of babies with TT as well as the frequency of frenotomy. Methods This cross‐sectional study included infants who initiated breastfeeding at birth and were referred for TT evaluation over a 14‐month period. Data were collected retrospectively by chart review and analyzed using SPSS. Factors associated with frenotomy were examined using logistic regression. Results Two hundred and forty‐one babies were referred. Ninety‐two percent (n = 222) were diagnosed with TT and 66.0% (n = 159) underwent frenotomy. In the multivariate model, nipple pain/trauma, inability to latch, inability to elevate tongue, and dimpling of tongue on extension were associated with frenotomy (P < 0.05). Most referrals in our region resulted in a diagnosis of TT; however, the number of referrals was lower than expected, and of these two‐thirds underwent frenotomy. Interpretation TT is a relatively common finding among breastfed infants. Future research should examine whether a simplified assessment tool containing the four items associated with frenotomy in our multivariate model can identify breastfed infants with TT who require frenotomy.